Falha muscular e duração da repetição na musculação: efeito sobre as respostas de hipertrofia, força muscular e atividade eletromiográfica - Lucas Túlio de Lacerda (2020)
Study 1: The aim of this study was to investigate the effects of muscle failure (MF) or not to MF (NMF) training on strength and muscle hypertrophy relative gains (average and individual data) as well as on normalized root mean square of the electromyographic signal (EMGRMS). Ten men untrained in resistance training participated in the study. Each leg was allocated in 1 of 2 unilateral training protocols (MF or NMF with equal volume) on knee extension exercise. Both protocols were performed with 3-4 sets, 3 minutes‟ rest, and 55-60% of one repetition maximum (1RM). Rectus femoris and vastus lateralis muscles cross-sectional area (CSA), maximal muscle strength (1RM and maximal voluntary isometric contraction), and muscular endurance (maximum number of repetition) were assessed before and after 14 weeks. In addition, neuromuscular activation by normalized root mean square of the electromyographic signal (EMGRMS) was measured in 2nd and 35th training sessions. The average results showed that both training protocols were similarly effective in inducing increases in strength and muscle hypertrophy gains. However, individual analysis data suggest that NMF protocol with equal volume may promote similar or even greater muscle hypertrophy (vastus lateralis) and muscular endurance performance when compared with MF protocol. Also, normalized EMGRMS responses analyzed during 2nd and 35th sessions were similar in MF and NMF protocols for rectus femoris and vastus lateralis muscles. In conclusion, MF and NMF protocol conducted with the same total repetition numbers produced similar maximal muscle strength performance and neuromuscular activation. Nevertheless, NMF training could be a more appropriate strategy to increase muscle hypertrophy (vastus lateralis) and muscular endurance performance in untrained individuals when compared with MF. Study 2: The aim of this study was to investigate the effects of two 14-week resistance training protocols each with a different repetition duration performed to muscle failure on gains in strength and muscle hypertrophy (average and individual data) as well as on normalized root mean square of the electromyographic signal (EMGRMS) and forceangle relationships. The left and right legs of ten untrained males were assigned to either one of the two protocols (2-s or 6-s RD) incorporating unilateral knee extension exercise. Both protocols were performed with 3-4 sets, 50-60% of the one-repetition maximum (1RM), and 3 min rest. Rectus femoris and vastus muscles cross-sectional areas (CSA), maximal voluntary isometric contraction (MVIC) at 30o and 90o of knee flexion and 1RM performance were assessed before and after training period. In addition, normalized EMG and force-angle relationships were assessed in the 2nd and 35th training sessions. The main results show that the 6-s RD protocol induced larger gains in MVIC in the 30o of knee angle measurement than the 2-s RD protocol. Increases in MVIC in the 90o of knee angle and 1RM were indifferent between the 2-s and 6-s RD protocols. For the rectus femoris muscle growth, inconclusive changes were found across the ten subjects. In contrast, the 2-s RD protocol may have resulted in superior vastus lateralis muscle hypertrophy. Moreover, different normalized EMG and force-angle values were detected between protocols over most of angles analyzed. Thus, performing longer RD could be a more appropriate strategy to provide greater gains in maximal muscle strength at shortened knee positions, although shorter RD would induce superior muscle hypertrophy.